Influence of Steel Fiber on the Shear Strength of a Concrete Beam - Hameed, Ali Ammar; Al-Sherrawi, Mohannad Husain (Civil Engineering Journal, 2018)
The shear failure in a concrete beam is a brittle type of failure. The addition of steel fibers in a plain concrete mix helps to bridge and restrict the cracks formed in the brittle concrete under applied loads, and enhances the ductility of the concrete. In this research an attempt was made to investigate the behavior and the ultimate shear strength of hooked end steel fiber reinforced concrete beams without traditional shear reinforcement. Four simply-supported reinforced concrete beams with a shear span-to-depth ratio of about 3.0 were tested under two-point loading up to failure. Steel fibers volumetric fractions that used were 0.0, 0.5, 0.75 and 1.0%. Test results indicated that using 1.0% volume fraction of hooked steel fiber led to exclude shear failure and enhanced the use of steel fibers as shear reinforcement in concrete beams. The results also showed that a concrete beam with hooked steel fiber provided higher post-flexural-cracking stiffness, an increase in the shear capacity and energy absorption and an increase in the maximum concrete and steel reinforcement strains.